Cristais Líquidos Ferroelétricos - CLF. Uma abordagem sintética - Merlo,Aloir A. (2001)
Synthetic methods used for the synthesis of the Ferroelectric Liquid Crystals (FLCs) will be considered with emphasis on the chiral synthesis methodologies and mesomorphic electrooptical properties.